A Discourse Analysis of Jokowi's International Speech Text: A Study on Critical Linguistics - Abisag Rina Situmorang; Dwira May Situmorangb; Imelda Oppusunggu; Novita Forena Simanungkalit; Veronika MR Silalahi; Herman Herman (Journal of English Language and Education, 2023)
The goal of this research is to identify and analyse the discourse analysis found in Jokowi’s international speech text. Descriptive qualitative was conducted in this research. Data Source Researchers feel the need to support the data as corroborating evidence that it was indeed Jokowi's speech based on what will be analyzed in this study Transcription of Jokowi's speech. It's a video taken from the internet www.youtube.com or rather at (https://youtu.be/k6lN2cweaOs). This video shows Jokowi giving a speech in Indonesian about an endless war that will harm future generations. The results show that the use of grammar based on choice of word, clause, lexical, and figure of speech are the ways to expose certain meaning based on who is the speaker and the effect to the listeners. The changes patterns of clause and sentence can be changed, exchanged, omitted, added, combined with other clauses and rearranged